2006
DOI: 10.1002/jcu.20240
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity and other factors that may affect the prevalence of echogenic intracardiac foci in the fetus

Abstract: We did not find any significant difference in the prevalence of EIF among the 4 different ethnic groups. The association between congenital anomalies and other sonographic markers should be studied further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
2
6
1
Order By: Relevance
“…In the study by Lim et al, which included four ethnic groups (Asian, Hispanic, black, and white), no significant difference in the prevalence of ICEF was found. 18 The rate of fetal aneuploidy was not found to be increased in association with ICEF in our study. Only one fetus was found to be level 3 mosaic for Trisomy 16.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In the study by Lim et al, which included four ethnic groups (Asian, Hispanic, black, and white), no significant difference in the prevalence of ICEF was found. 18 The rate of fetal aneuploidy was not found to be increased in association with ICEF in our study. Only one fetus was found to be level 3 mosaic for Trisomy 16.…”
Section: Discussioncontrasting
confidence: 53%
“…7,[13][14][15] Certain studies suggested a higher incidence of ICEF in the Asian population 16,17 but other studies reported no significant difference in prevalence of ICEF in various ethnic groups. 18 There are no data available from India in this context. The purpose of this retrospective study was to determine the prevalence of ICEF and to describe the association of an intracardiac echogenic focus, with or without other associated risk factors to the fetal outcome in a population referred to our prenatal diagnostic division over a 2-year period.…”
mentioning
confidence: 96%
“…The prevalence of ICEF in this study was 3.4%, a value that does not differ significantly from those of previously reported studies. For example, prevalence values ranging from 0.5 to 12% have been reported for the overall prenatal population (11–14). Our observation was also in close agreement with the previous findings that an ICEF was more easily identified in the apical view than in the lateral view (11).…”
Section: Discussionmentioning
confidence: 99%
“…Asian ethnicity in particular, was associated with an increased detection rate of this finding [5,[17][18][19][20]. For example, Shipp et al [5] detected echogenic intra-cardiac foci in as many as 30% of the Asian fetuses, suggesting that this finding is a normal variant rather than a marker for anomaly in this population.…”
Section: Introductionmentioning
confidence: 91%